2003
DOI: 10.1021/ic0341845
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of A-α-[SiNb3W9O40]7- by pH-Controlled Formation of Individual Nb−μ-O−Nb Linkages

Abstract: The reversible, stepwise formation of individual Nb-mu-O-Nb linkages during acid condensation of 2 equiv of A-alpha-[SiNb(3)W(9)O(40)](7-) (1) to the tri-mu-oxo-bridged structure A-alpha-[Si(2)Nb(6)W(18)O(77)](8-) (4) is demonstrated by a combination of X-ray crystallography and variable-pD solution (183)W and (29)Si NMR spectroscopy. Addition of DCl to a pD 8.4 solution of 1 (Li(+) salt in D(2)O) results in formation of a mono-Nb-mu-O-Nb-linked dimer, A-alpha-[Si(2)Nb(6)W(18)O(79)](12-) (2; pD = 3.0-1.3). At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 38 publications
1
30
0
2
Order By: Relevance
“…Ionic strength was varied by additions of NaCl, and reported ionic-strength values include contributions from the Keggin ion salts. pD values of D 2 O solutions were calculated using pD = pH el + 0.4, where pH el values are readings from standard pH electrodes immersed in the D 2 O solutions [14,15].…”
Section: Aqueous Electrolyte Solutionsmentioning
confidence: 99%
“…Ionic strength was varied by additions of NaCl, and reported ionic-strength values include contributions from the Keggin ion salts. pD values of D 2 O solutions were calculated using pD = pH el + 0.4, where pH el values are readings from standard pH electrodes immersed in the D 2 O solutions [14,15].…”
Section: Aqueous Electrolyte Solutionsmentioning
confidence: 99%
“…If the solution of the reactants were left to heat at 90 °C for less than 2 h, we have been unable to isolate single crystals of compound 1 , however, it was found that there was no obvious increase in the yields when the heating time was more than 4 h. In addition, the reaction is not particularly sensitive to the amount of Eu III because 1 could be obtained with the mole ratios of Eu III /Nb 6 ranging from 6:1 to 16:1, with 10:1 giving the highest yield. It is worth mentioning here that compounds 1 − 8 can be isolated without the need for extra cations, different from an essential templating role of Cs + in the formation of Keggin and Wells-Dawson-type niobium-substituted polyoxotungstates 2831, 4143 .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, most of the reported TM-containing PONb derivatives are synthesized by hydrothermal or hydrothermal-diffusion methods. In contrast, some Nb-substituted polyoxotungstates of the classic Lindqvist or Keggin derivatives has been produced under acidic solution in the presence of H 2 O 2 2831 . Recently, we have successfully manipulated the reaction of Nb 6 cluster under acidic condition by an in-situ synthetic strategy 1922 .…”
Section: Introductionmentioning
confidence: 99%
“…Materials Cs 6 H[Si(NbO 2 ) 3 W 9 O 37 ]·8 H 2 O was synthesized according to the procedure described in the literature, [10] and the powder product was used without further purification. The material was characterized by IR spectroscopy and elemental analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, these clusters are soluble in water and could be viewed as the smallest nanoparticles with ordered structures at the atomic level. [10] We propose that by sandwiching of transition-metal cations, visible-light-active photocatalysts may be achieved. [5] During the past few years, the photocatalytic H 2 evolution activity of polyoxotungstates has been studied.…”
mentioning
confidence: 99%